Effect of 5% lidocaine-medicated plaster in preventing chronic postsurgical pain after knee replacement: protocol for a randomized double-blind placebo-controlled trial - Yuan, Junpeng; Xu, Huichan; Guo, Jiongjiong; Li, Yan; Yu, Youjia; Jin, Xiaohong (Frontiers in Pharmacology, 2024)
Background With an aging population, knee arthroplasty is increasingly common; however, chronic postsurgical pain (CPSP) affects up to 30% of patients. This study aims to evaluate the efficacy of 5% lidocaine-medicated plaster (LP5) in preventing CPSP among patients undergoing knee arthroplasty. Methods This is a dual-center, randomized, double-blind, placebo-controlled trial involving 128 adult patients scheduled for knee arthroplasty. Participants will be randomly assigned, stratified by center, to either the LP5 group or the placebo group (n = 64 per group). The LP5 or placebo group will apply the patch 1 day before surgery and on postoperative days 1–3, with multimodal analgesia administered postoperatively. Multimodal analgesia will include intraoperative flurbiprofen axetil and postoperative patient-controlled sufentanil. The primary outcome is the pain subscale of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) at 3 months postoperatively. Secondary outcomes will include WOMAC stiffness, function, and total scales; Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) Pain Scale; 36-Item Short Form Health Survey (SF-36); postoperative pain scores; Visual Analog Scale (VAS) sleep scores; postoperative sufentanil consumption; need for rescue analgesia; length of Post-Anesthesia Care Unit (PACU) stay; length of hospital stay; and 90-day mortality. Safety outcomes will include assessments of hypotension, hypertension, bradycardia, tachycardia, arrhythmia, interventions for haemodynamic events, headache, dizziness, nausea, vomiting, local skin allergy, wound infection, and toxic reaction. Data will be analyzed following a modified intention-to-treat approach. Discussion This study aims to provide high-quality evidence for the efficacy and safety of LP5 in preventing CPSP in patients undergoing knee arthroplasty.